Rozwój regionalny i lokalny w warunkach gospodarki i konkurencji globalnej oraz metropolizacji przestrzeni - Kot, Janusz (Regional and Local Development in Terms of Global Economy, Competition and Metropolization of Space, 2006)
Management of regional and local development is evolving simultaneously with the process of globalization of economy and increasing competition. Changeability of internal and external circumstances of growth implicates a need for researching new factors influencing regional and local development as well as spatial organization. This article is an attempt to identify main issues connecting regional competitiveness in global market economy with the growing role of metropolitan areas in space organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 17-26